Sticky assessments: The impact of teachers' grading standard on pupils' school performance - Tamás Keller (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
This paper argues that school grades cannot be interpreted solely as a reward for a given school performance, since they also reflect teachers' ratings of pupils. Grades therefore contain valuable information about pupils' own - usually unknown - ability. The incorporated assessment in grade might be translated into self-assessment, which could influence the effort that pupils invest in education. Getting discounted grades in year 6 for a given level of math performance assessed using a PISA-like test has a positive effect on math test scores in year 8 of elementary education and also influences later outcomes in secondary education. The empirical analysis tries to minimize the possible bias caused by the measurement error in year 6 test scores (unmeasured ability) and employs classroom fixed-effect instrumental variable (IV) regression and difference-in-difference models. The main analysis is based on a unique Hungarian individual-level panel dataset with two observations about the same individual - one in year 6 (12/13 years old) and again two years later, in year 8 (14/15 years old) of elementary education. The data for three entire school cohorts is analyzed - approximately 140,000 individuals.
Keywords: I20; I21; J24; 330; School performance; Inflated school grades; Feedback; Good teacher; Educational panel data; Hungarian National Assessment of Basic Competencies